Isolasi dan Karakterisasi Asam Laurat dari Minyak Kelapa Sebagai Aplikasi Sel Surya Berbasis Cristal Cair: Isolasi dan Karakterisasi Asam Laurat dari Minyak Kelapa Sebagai Aplikasi Sel Surya Berbasis Cristal Cair - Al Jalali Muhammad; Muhammad Anas; Ratna; Darnia Sari (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2021)
This study aims to determine the effect of KOH concentration on crystal structure, functional groups, and surface morphology of lauric acid extracted from coconut oil. The first stage is lauric acid extracted from coconut oil. The results of lauric acid were analyzed using three tools namely XRD (X-Ray Diffraction) which was useful to know the structure of lauric acid crystals, FTIR (Fourier Transform InfraRed) to determine the functional groups of lauric acid and SEM (Scanning Electron Microscopy) to determine the morphology of the surface of lauric acid. The results of XRD analysis at an angle of 2θ, the higher the KOH concentration, the clearer the diffraction peak at an angle of 2θ = 22 ° (002) which characterized lauric acid (C12) which had a monoclinic crystal structure and the results of the FTIR analysis, the higher the KOH concentration, showed the absorption at the number waves 1640.59 cm-1, 1637.03 cm-1, and 1647.89 cm-1 were not much different that have carbonyl functional groups (C = O) which were functional groups of lauric acid (C12).